Clinical and functional status of patients with severe COVID-19 pneumonia: an observational study at 2–3 months following discharge - Castillo Sánchez, Inmaculada; Camarasa, Julia Tárrega; Barbeta Sánchez, Enric; Oliveira, Vinicius Rosa (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Critically ill COVID-19 patients present long-term sequelae that affect their everyday life. This study aimed to describe the clinical and functional status of patients with severe COVID-19 pneumonia at 2-3 months post discharge from a Spanish critical care unit.Methods: We collected retrospective data from 58 patients admitted to the critical care unit with diagnosis of severe respiratory failure due to COVID-19. Only patients who required invasive (IMV) or noninvasive ventilation (NIV) during their hospital stay were included. The following data were collected 2-3 months after hospital discharge: respiratory signs and symptoms, lung ultrasound (LUS) and diaphragm ultrasound images, blood test analysis, lung function parameters (spirometry and DLCO), exercise capacity (6-minute walk test and sit-to-stand test), level of physical activity and health-related quality of life.Results: We found clinical symptoms and lung structural alterations in LUS images of 26 patients (48.1%). Those presenting LUS abnormalities had longer length of stay in hospital (p=0.026), functional alterations in spirometry (p<0.01) and decreased diaphragm excursion (p=0.029). No This is a provisional file, not the final typeset article significant alterations were observed in blood test analysis, exercise capacity, level of physical activity and health-related quality of life.Conclusions: A significant part of the patients admitted to a critical care unit continue to present clinical symptoms, pulmonary morphological abnormalities, and lung function alterations 2-3 months post discharge. This study corroborates that assessing the functional status of the survivors is essential to monitor the evolution of pulmonary sequelae.